Laboratory- to field-scale investigations to evaluate phosphate amendments and Miscanthus for phytostabilization of lead-contaminated military sites - Alasmary, Zafer Saad (Kansas State University, 2020)
Potentially toxic substances can contaminate extensive areas of productive land due to military activities. The most common and widespread metal contaminant in military lands is lead (Pb). The main objectives of this study were to evaluate the feasibility of using Miscanthus, a second-generation biofuel crop, for photostabilization of Pb in contaminated military site soils; the effect of soil amendments on Miscanthus growth; and the effects of continual plant growth, nutrient removal and the soil chemical changes induced by Miscanthus growth on soil Pb bioaccessibility. In 2016, we established a field site on a US Army reservation in Fort Riley, KS. Miscanthus was planted in an area with soil total Pb concentration ranging from 900 – 1,500 mg kg⁻¹ and near-neutral soil pH. Five treatments were evaluated: (i) control plots without tillage with existing vegetation, (ii) no-tillage, no additional amendments planted with Miscanthus, (iii) tilled soil, no additional amendments planted with Miscanthus, (iv) tilled soil amended with triple superphosphate (at 5:3 Pb:P molar ratio) planted with Miscanthus, and (v) tilled soil amended with organic P source (class B biosolids applied at 45 Mg/ha ) planted with Miscanthus. Results from three years show that one-time addition of soil amendments to Pb-contaminated soil supports establishing and stabilizing Miscanthus, increasing biomass yield as well as reducing phytoavailability and bioaccessibility of Pb. Plots amended with biosolids had significantly less total Pb uptake, plant tissue Pb concentration, and Pb bioaccessibility, and more soil enzyme activities, organic carbon, and microbial biomass. Controlled-environment greenhouse and laboratory incubation studies were conducted to test selected additional P sources. Additional sources included non-traditional, less soluble types such as struvite and apatite. The greenhouse study aimed to evaluate the effect of Miscanthus growth on bioaccessibility of amended and non-amended soils and the effect of soil amendments on soil-plant transfer of soil Pb over three Miscanthus cuttings. Soil amendments increased dry matter yield in the first cutting. Soils in Miscanthus pots that were amended with biosolids, had significantly lower total Pb uptake, Pb concentration in plant tissues, and Pb bioaccessibility when compared to the control across all cuttings. Overall, the results suggested that Miscanthus can be effectively and safely grown on Pb-contaminated soils amended with biosolids. The incubation study evaluated the effectiveness of various in situ P treatments on reducing Pb bioaccessibility and the effects of different P sources on the speciation of soil Pb over time. X-ray absorption spectroscopy was used to understand treatment-induced changes to soil Pb speciation. Results showed that soil pH decreased slightly for all treatments. Percent of bioaccessible Pb in soils amended with biosolid were significantly (α=0.05) less than the other amendments. The high rate of biosolids (225 Mg ha⁻¹) was the most effective in controlling the bioaccessibility of soil Pb, and the reductions in bioaccessibility ranged from 63 to 76% compared to the control. X-ray absorption spectroscopy results indicated pyromorphite (stable Pb phosphates) phases were the most dominant Pb species in both amended and non-amended soils. The results of these studies suggest that Miscanthus can be grown successfully in Pb-contaminated shooting range soils in combination with organic or inorganic phosphate amendments, while minimizing the associated environmental risks.
Keywords: Miscanthus; Skeet range; Photostabilization; Biofuel crop; Lead; Bioaccessibility